Multidimensional Targeting and Evaluation: A General Framework with an Application to a Poverty Program in Bangladesh - Virginia Robano; Stephen C. Smith (Institute for the Study of Labor (IZA), 2013)
Many poverty, safety net, training, and other social programs utilize multiple screening criteria to determine eligibility. We apply recent advances in multidimensional measurement analysis to develop a straightforward method for summarizing changes in groups of eligibility (screening) indicators, which have appropriate properties. We show how this impact can differ across participants with differing numbers of initial deprivations. We also examine impacts on other specially designed multidimensional poverty measures (and their components) that address key participant deficits. We apply our methods to a BRAC ultra-poverty program in Bangladesh, and find that our measures of multidimensional poverty have fallen significantly for participants. This improvement is most associated with better food security and with acquisition of basic assets (though this does not mean that the cause of poverty reduction was program activities focused directly on these deficits). In general, we find that the BRAC program had a greater impact on reducing multidimensional poverty for those with a larger initial number of deprivations. We also showed how evaluation evidence can be used to help improve the selection of eligibility characteristics of potential participants.
Keywords: O15; I32; 330; poverty; multidimensional poverty; poverty alleviation strategies; BRAC; microfinance institutions; ultra-poverty; ultra-poor; CFPR/TUP; Bangladesh; difference-in-difference; impact assessment; program evaluation; counterfactual targeting; assignment errors